The Impact of Digital Transformation on The Digital Literacy Skills of Dayak Adolescents In Central Kalimantan - Siti Juhairiah; Doddy Teguh Yuwono; Anggelina Hariyanti (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Aim: This study aims to explore the impact of digital transformation on the digital literacy skills of Dayak adolescents in Central Kalimantan, focusing on key aspects such as social media usage, internet information search, information evaluation, online privacy, and content sharing ethics. Method: The research employed a quantitative approach with a survey method, where data were collected through a structured questionnaire based on demographic variables such as gender, age, education level, and ethnicity. A total of 300 Dayak adolescents were selected using purposive sampling techniques. The data were analyzed using SPSS version 26 to identify significant factors influencing digital literacy. Result and Disscusions: The results indicate that gender is the most significant demographic factor affecting digital literacy, with females outperforming males in terms of digital skills (r = -0.154, p = 0.007). The study suggests that females tend to use technology more effectively for searching and evaluating information. However, age (r = 0.102, p = 0.041) and education level (r = 0.043, p = 0.365) did not show a significant influence on digital literacy, as evidenced by the ANOVA tests (F = 1.562, p = 0.211 for age; F = 1.003, p = 0.368 for education). This finding implies that access to and experience with digital technology is relatively uniform across different age groups and educational backgrounds.Furthermore, there was no significant relationship between social media usage and digital literacy (r = -0.054, p = 0.211), which may be due to the predominant use of social media for entertainment rather than educational or informational purposes. Conclusion: The study concludes that gender differences must be considered in designing digital literacy programs, and there is a need to encourage more purposeful and critical use of digital technologies among adolescents.